텍스트 재구성을 통한 한국어 읽기 자료 구성 방안 연구 - 이명희(Myung-Hee Lee) (한국어문화교육, 2011)
외국어 학습에서 읽기는 언어와 정보 획득 외에도 문화를 수용하는 과정에서 가장 큰 비중을 차지한다. 학문적 목적 한국어의 읽기 교육에서 특히 중급 단계 이후 학습자들은 과거 읽기 교육의 목적이었던 정확한 읽기 능력을 기르는 것과 함께 텍스트를 빠른 속도로 읽어내야만 한다. 이를 위해서는 전문 교육 과정 안에서 학습자에게 제공되는 텍스트의 역할이 무엇보다 중요하다. 현재 읽기 교육에서 텍스트는 학습자들에게 읽기 과정과 이해에 미치는 요인들에 대한 고려가 제대로 이루어지지 않고 주어진 텍스트를 읽고 텍스트 내용을 이해, 점검하는 과정으로만 대부분 그 역할을 다해왔다. 따라서 본 연구는 읽기 수업에서 학습 단계나 수준에 맞지 않는 텍스트에 대해 단순화 및 상세화를 거친 텍스트의 재구성이 필요함을 인식하고, 한국어 학습자들에게 제공되는 읽기 텍스트에 대한 이해와 읽기 능력 향상을 위해 중급 단계 학습자를 대상으로한 자료 구성 방안을 찾는 데 그 목적이 있다. 이를 위해 텍스트에 대한 요구 조사를 시행한 뒤, 현행 읽기 교재의 텍스트에서 단순화와 상세화가 어떻게 나타나는지 살펴본 뒤 직접 텍스트 재구성을 해보고자 한다. This study's goal is to construct teaching materials which helps intermediate Korean learners to improve text understanding and reading capability. To do so, this study investigates problems upon the learner needs analysis and reading text analysis, the study suggests proper method for organizing Korean Reading Materials. Text modification is a method to simplify or to elaborate original text, in order to ease the reading understanding for learners. As we examining this study, in Chapter 2, the study mentions concepts of reading, and emphasized the neccesity of text modification in relationships between reading education and teaching materials. In Chapter 3, to investigate Korean reading material, the study performed divided surveys on learner's need with reading text in class, and the opposite. Also, by analyzing present intergrated teaching materials, the study shows how simplification and elaboration occurs in text modification method. In Chapter 4, the study suggests how simplification and elaboration of text could be text modification by presenting actual expamples.